Feasibility and safety of expandable mediastinoscopic and laparoscopic radical esophagectomy - Zhang, Weidong; Cui, Dong; Shi, Kefeng; Chen, Maolin; Zhang, Binbin; Qian, Rulin (Frontiers in Oncology, 2023)
Background: At present, minimally invasive radical esophagectomy is the main surgical method for esophageal cancer treatment, but it has inherent limitations. We have developed a novel method of radical esophagectomy without thoracotomy to improve this situation, namely, by using EMLE. We evaluated the feasibility and safety of expandable mediastinoscopic and laparoscopic radical esophagectomy (EMLE) through a retrospective analysis. Methods: From January 2019 to June 2022, we successfully performed 106 cases of radical resection of esophageal cancer with this new surgical technique, gradually improved the surgical path, and recorded the perioperative data and postoperative complications of all patients. Results: The operation was successfully performed in all patients except for two patients who required a switch to open surgery. The mean operation time was 171.11±33.29 min and the mean intraoperative blood loss was 93.53 ±56.32 mL. The mean number of removed lymph nodes was 23.59±5.42. The postoperative complications included pneumonia (3.77%), recurrent laryngeal nerve palsy (1.89%), anastomotic leak (14.15%), pleural effusion (5.66%), chylothorax (2.83%), and reoperation (4.72%). All complications were graded I–III per the Clavien–Dindo classification. No perioperative death was recorded. Conclusions： Expandable mediastinoscopic and laparoscopic radical esophagectomy is feasible for radical resection of esophageal cancer, with good therapeutic effect and safety. Because of its minimal impact on patients and convenient operation, it is a novel surgical option for patients with esophageal cancer and is expected to become a standard surgical method for radical esophagectomy in the future.